Multicultural Value Integration in Islamic Education Learning Practices: Integrasi Nilai Multikultural dalam Praktik Pembelajaran Pendidikan Islam - Amin, Nashikhun; Astutik, Anita Puji (Indonesian Journal of Education Methods Development, 2025)
General Background Multicultural education has become a central discourse in contemporary Islamic education due to increasing social diversity and the urgency of strengthening tolerance-based character formation. Specific Background In the context of Islamic Religious Education, the integration of multicultural values is expected to foster inclusive attitudes, religious moderation, and respect for cultural differences within educational institutions. Knowledge Gap However, practical implementation models that systematically integrate multicultural principles into Islamic Religious Education learning remain underexplored in specific institutional contexts. Aims This study aims to analyze and describe the integration of multicultural values in Islamic Religious Education learning processes. Results The findings indicate that multicultural values are integrated through learning planning, classroom implementation, and the development of school culture that promotes tolerance, inclusivity, and mutual respect. Novelty The study provides contextual empirical evidence on structured integration patterns of multicultural Islamic education within formal learning settings. Implications These findings contribute to the development of Islamic education curriculum design and provide a reference framework for strengthening character education grounded in multicultural and religious moderation principles. Keywords: Multicultural Education, Islamic Religious Education, Religious Moderation, Curriculum Integration, Character Formation Key Findings Highlights Multicultural principles are embedded in lesson planning and instructional strategies. Classroom activities reflect tolerance-based and inclusive learning culture. School environment supports diversity-oriented character development.